Gamma-D crystallin gene (CRYGD) mutation causes autosomal dominant congenital cerulean cataracts. Issue 4 (1st April 2003) - Nandrot, E; Slingsby, C; Basak, A; Cherif-Chefchaouni, M; Benazzouz, B; Hajaji, Y; Boutayeb, S; Gribouval, O; Arbogast, L; Berraho, A; Abitbol, M; Hilal, L
Abstract : Congenital cataracts are a major cause of bilateral visual impairment in childhood. We mapped the gene responsible for autosomal congenital cerulean cataracts to chromosome 2q33–35 in a four generation family of Moroccan descent. The maximum lod score (7.19 at recombination fraction θ=0) was obtained for marker D2S2208 near the γ-crystallin gene ( CRYG ) cluster. Sequencing of the coding regions of the CRYGA, B, C, and D genes showed the presence of a heterozygous C>A transversion in exon 2 of CRYGD that is associated with cataracts in this family. This mutation resulted in a proline to threonine substitution at amino acid 23 of the protein in the first of the four Greek key motifs that characterise this protein. We show that although the x ray crystallography modelling does not indicate any change of the backbone conformation, the mutation affects a region of the Greek key motif that is important for determining the topology of this protein fold. Our data suggest strongly that the proline to threonine substitution may alter the protein folding or decrease the thermodynamic stability or solubility of the protein. Furthermore, this is the first report of a mutation in this gene resulting in autosomal dominant congenital cerulean cataracts.